PERLAKUAN AKUNTANSI PENGELOLAAN LIMBAH DALAM LAPORAN KEUANGAN PADA RUMAH SAKIT JEMBER KLINIK - Norita Citra Yuliarti (Universitas Muhammadiyah Jember, 2017)
Abstract: The purpose of this study was to examine the method of recording financial statements Jember Clinic Hospital is already implementing environmental accounting system in terms of the allocation of the cos tof waste management with accounting theory existing environment. The data obtained in this study were obtained either through interviews, documentation and observation. Once all the required data or information collected in this study, then presented and analyzed with descriptive-qualitative manner. Data analysisis done by comparing the financial statements presented Jember Clinic Hospital with accounting theory existing environment.Keywords: Environmental Accounting, Hospitals, Waste Management Costs